Cheddar off dead - Moss, Korina (Moss, Korina. Cheese shop mystery, 2022)
"Cheesemonger Willa Bauer is proving that sweet dreams are made of cheese. She's opened her very own French-inspired cheese shop, Curds & Whey, in the heart of the Sonoma Valley. The small town of Yarrow Glen is Willa's fresh start, and she's determined to make it a success--starting with a visit from the local food critic. What Willa doesn't know is that this guy never gives a good review, and when he shows up, nothing goes according to plan. She doesn't think the night can get any worse...until she finds the critic's dead body, stabbed with one of her shop's cheese knives. Now a prime suspect, Willa has always believed life's problems can be solved with cheese, but she's never tried to apply it to murder..."--Back cover.